Varicella-Zoster Virus (Chickenpox): Nursing, Laboratory, and Epidemiological Perspectives - Alnami, Abbas Mohammed; Ahmed Ibrahim Hussein Alnajie; Mohammed Ahmed AMohammed Okayri; Layla Yahya Mansour Matary; Kamlah Mortada Ahmad Alhazm; Fatimah Ahmad Abdo Suraihi; Nouf Ali Ahmed Nahari; Hussain Ebrahim Tawashi; Rajaa Ibrahim Ahmed Alakrash; Muteeb Mohamed Alasiri; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Varicella (chickenpox) is a highly contagious viral disease caused by the varicellazoster virus (VZV), characterized by a generalized vesicular rash and systemic symptoms. Despite widespread vaccination, varicella continues to pose clinical and public health challenges, particularly among highrisk populations such as adults, pregnant women, neonates, and immunocompromised individuals. Aim: This article aims to comprehensively review varicella from nursing, laboratory, and epidemiological perspectives, emphasizing etiology, transmission, clinical features, diagnosis, management, prevention, and public health implications. Methods: A descriptive narrative review approach was used, synthesizing established clinical, epidemiological, and laboratory data on VZV infection. Key aspects reviewed include pathophysiology, histopathology, clinical presentation, diagnostic modalities, treatment strategies, complications, and prevention through vaccination. Results: Varicella is primarily transmitted via airborne droplets and direct contact with vesicular fluid. While generally selflimiting in children, severe disease and complications such as pneumonia, encephalitis, and secondary bacterial infections are more common in adults and immunocompromised hosts. Polymerase chain reaction testing is the most sensitive diagnostic method. Antiviral therapy reduces disease severity in highrisk patients, and vaccination has significantly decreased incidence, hospitalizations, and mortality. Conclusion: Varicella remains a clinically relevant disease requiring ongoing surveillance, vaccination advocacy, early diagnosis, and interprofessional collaboration to minimize complications and transmission.